Remember me memory and forgetting in the digital age - Sisto, Davide 1978-; Kilgarriff, Alice (Cambridge, United Kingdom Polity Press, 2021)
As the end of December draws near, Facebook routinely sends users a short video entitle 'Your year on Facebook.' It lasts about a minute and brings together the images and posts that received the highest number of comments and likes over the last year. The video is rounded off with a message from Facebook that reads: 'Sometimes, looking back helps us remember what matters most. Thanks for being here.'

It is this 'looking back,' increasingly the focus of social networks, that is the inspiration behind Davide Sisto's brilliant reflection on how our relationship with remembering and forgetting is changing in the digital era. The past does not really exist: it is only a story we tell ourselves. But what happens when we tell this story not only to ourselves but also to our followers, when it is recorded not only on our social media pages but also on the pages of hundreds or thousands of others, making it something that can be viewed and referenced forever? Social media networks are becoming vast digitals archives in which the past merges seamlessly with the present, slowly erasing our capacity to forget. And yet at the same time, our memory is being outsourced to systems that we don't control and that could become obsolete at any time, cutting us off from our memories and risking total oblivion.

This timely and thoughtful reflection on memory and forgetting in the digital age will be of interest to students and scholars in media studies and to anyone concerned with the ways our social and personal lives are changing in a world increasingly shaped by social media and the internet.
Introduction. Social networks and looking back -- From social networks to digital archives -- Collective cultural autobiographies and encyclopedias of the dead 2.0 -- Total recall, digital immortality, retromania -- Conclusion. Digital inheritance and a return to oblivion.
Originally published in Italian as Ricordati di me: La rivoluzione digitale tra memoria e oblio (c) 2020 Bollati Boringhieri editore, Torin"--Title page verso.
Includes bibliographical references (pages 138-147) and index (pages 148-155).
Purchased: Golden Books (17 September 2022); Selected at the Manila International Book Fair 2022.
Keywords: Online social networks; Internet -- Social aspects; Memory -- Social aspects; Social media -- Social aspects